Semeando modos de ensino e aprendizagem De moda - experiências de estágio Como questão - FLORI, Rogério Justino (2012)
This research analyzes how a group of students from two Fashion Design courses construct different ways of seeing fashion while dislocating and displacing between distinct learning spaces. Daily practices, classroom experiences and in-service student training activities are the learning spaces which concentrate the focus of this investigation. The data was gathered through periods of monitoring and observation in places where they developed in-service student training, field notes, interviews, conversation groups and photographic records. The research discusses student s expectations in relation to their professional training and anxieties that accompany their experiences in this period. It also discusses the negotiations and concessions they face in order to carry out their goals and studies while transiting across daily tasks, classrooms and in-service training activities. The axis of analysis of this research concentrate on the relations between technical and artistic learning, contradictions about the student role as in service trainee, coping with managers, colleagues and staff characterizing the experiences lived by the collaborators. The discussion about selected looks that the students wished to have created enhances the investigation understanding about ways of thinking the professional practice of fashion designers and their future desires.